Role of femoral artery ultrasound imaging in cardiovascular event risk prediction in a primary prevention cohort at a medium-term follow-up. Issue 5 (May 2020) - Kocyigit, Duygu; Gurses, Kadri Murat; Taydas, Onur; Poker, Ahmet; Ozer, Necla; Hazirolan, Tuncay; Tokgozoglu, Lale
Highlights: The predictive role of femoral artery ultrasonography on cardiovascular outcomes was evaluated. Femoral artery plaque characteristics were associated with increased risk of major adverse cardiac events. This persisted when adjusted for other imaging markers of atherosclerosis. Femoral artery plaque characteristics may be useful in primary prevention. Abstract: Background: Cardiovascular (CV) disease prevention guidelines have addressed how imaging may influence CV risk determined by established risk score systems in primary prevention. Nevertheless, data are lacking regarding the use of femoral artery ultrasonography for CV risk modification. Herein, we hypothesized that femoral artery plaque and its characteristics, as well as femoral intima-media thickness (fIMT) measurements, may predict major adverse cardiovascular events (MACE). Methods: Subjects free from documented CV disease who were scheduled for coronary computed tomographic angiography at our institution from September 2016-June 2017 were included. IMT measurements and plaque assessment were performed at femoral and carotid arteries. Coronary artery calcium score (CACS) was recorded. Patients were followed-up for MACE. Results: A total of 215 subjects (mean age: 54.85 years, 47.91% male) were eligible. Median number of CV risk factors was 3. Median 10-year atherosclerotic CV disease risk based on Pooled Cohort Equation (PCE) equation was 6.3%. At a median follow-up of 24 months, 9 subjects (4.19%) had MACE. Patients who experienced MACE at follow-up were older ( p = 0.047), more of male gender ( p = 0.015), had higher serum creatinine levels despite being within reference limits ( p = 0.031) and PCE equation risk score ( p = 0.011). In patients who experienced MACE at follow-up, distal ( p = 0.027), bifurcation ( p = 0.007), and proximal carotid IMT ( p = 0.030) and fIMT ( p = 0.015) were increased. Surface irregularities and ulceration in femoral artery plaques were more common ( p = 0.001) and CACS was higher ( p < 0.001). When adjusted for other subclinical atherosclerosis imaging markers, femoral artery plaque surface irregularities and ulceration and only coronary calcification (without concomitant carotid or femoral atherosclerosis) were found to be independent predictors of MACE at follow-up (both p = 0.004). Conclusions: Our data emphasize that baseline ultrasonographic assessment of the femoral arteries to define plaque characteristics may provide prognostic information for predicting MACE in a primary prevention cohort.